Five Indigenous Plants of Pakistan with Antinociceptive, Anti-Inflammatory, Antidepressant, and Anticoagulant Properties in Sprague Dawley Rats. (23rd November 2017) - Ismail, Hammad; Rasheed, Ammara; Haq, Ihsan-ul; Jafri, Laila; Ullah, Nazif; Dilshad, Erum; Sajid, Moniba; Mirza, Bushra
Abstract : Five medicinal plants of Pakistan were investigated for their antinociceptive, anti-inflammatory, antidepressant, and anticoagulant potential. Antinociceptive activity was estimated by hot plate and writhing assay. In hot plate assay, Quercus dilatata (52.2%) and Hedera nepalensis (59.1%) showed moderate while Withania coagulans (65.3%) displayed a significant reduction in pain. On the other hand, in writhing assay, Quercus dilatata (49.6%), Hedera nepalensis (52.7%), and Withania coagulans (62.0%) showed comparative less activity. In anti-inflammatory assays crude extracts showed significant edema inhibition in a dose dependent manner. In carrageenan assay, the highest activity was observed for Withania coagulans (70.0%) followed by Quercus dilatata (66.7%) and Hedera nepalensis (63.3%). Similar behavior was observed in histamine assay with percentage inhibitions of 74.3%, 60.4%, and 63.5%, respectively. Antidepressant activity was estimated by forced swim test and the most potent activity was revealed by Withania coagulans with immobility time 2.2s (95.9%) followed by Hedera nepalensis with immobility time 25.3s (53.4%). Moreover, the crude extracts of Fagonia cretica (74.6%), Hedera nepalensis (73.8%), and Phytolacca latbenia (67.3%) showed good anticoagulant activity with coagulation times 86.9s, 84.3s, and 67.5s, respectively. Collectively, the results demonstrate that these five plants have rich medicinal constituents which can be further explored.